Stable Isotopes and Hydrochemistry Approach for Determining the Salinization Pattern of Shallow Groundwater in Alluvium Deposit Semarang, Central Java - Satrio, Satrio; Prasetio, Rasi; Hadian, Muhamad Sapari Dwi; Syafri, Ildrem (Indonesian Journal on Geoscience, 2017)
DOI: 10.17014/ijog.4.1.1-10A groundwater study has been conducted in the Semarang City in August 2014, aiming to determine the source of shallow groundwater salinization using stable isotopes (18O, 2H) and water chemistry approach, and supported by local hydrogeological data. A number of shallow groundwater samples were taken at several locations with a depth of 0 - 35 m. Based on geological data, shallow groundwater of Semarang alluvium is dominated by insertion of sand-gravel and sandy-clay with average porosity of around 56.0 %. This layer is thinning towards the south and then increasingly thickening to the north and north-east of the studied area. The results of the analyses show that the characteristics of shallow groundwater, i.e. approximately 51% of groundwater, still have the original composition as meteoric water and the remaining approximately 49% obtained a shift in the isotopic composition as caused by interaction with seawater and the little influence of evaporation. The results of chemical analysis of water indicates that in dry seasons, shallow groundwater aquifers in the Semarang City is dominated by chloride (Cl-) with NaCl of water type. While the parameters of bicarbonate, chloride, and Na/Cl ratio, shallow groundwater can be classified into two groups, namely unintruded groundwater around 51% spread from the foot hills to the south towards the hills with elevations of 9 - 142 m above sea level and intruded groundwater around 49% spread from the coastline to the urban direction.